The Dielectric Properties of Nano Al2O3 Hybrid Polyesterimide - FAN Yong; GUO Jia; CHEN Hao; YANG Rui-xiao; YANG Shu-yu (Journal of Harbin University of Science and Technology)
In order to improve the corona resistance properties of polyesterimide resin, nanoAl2O3 sol was prepared by microemulsionhydrothermal method and dispersed into polyesterimide resin solution by mechanical blending, then nanoAl2O3 hybrid polyesterimide composite material was prepared The results show that the nanoparticles are dispersed in the polyesterimide matrix; With the increase of doping amount, the corona resistance of the composites increases, but the dielectric strength decreases; When the doping amount was 12%, its coronaresistant life is 5 times more than pure polyesterimide resin, and the dielectric strength is 1752kV/mmWith the increase of the doping amount, the dielectric loss of the material is little affected, but the dielectric coefficient increases slightly The nanoAl2O3 particles in matrix have little effect on the heat resistance of the material